Pengaruh Finger Print Terhadap Produktivitas Kinerja Karyawan Bank Syariah Indonesia (BSI) Bojonegoro - Agnisa Widayanti (https://journal.metanusantara.com/jenius/index.php/jem, 2025)
This study aims to examine the relationship between employee attendance rates and work productivity at BSI Bojonegoro, as well as to identify the underlying factors contributing to absenteeism and their impact on performance. A quantitative approach was employed, utilizing a survey method and simple linear regression analysis. Data were collected from 120 purposively selected respondents. The analysis revealed that the research instrument demonstrated high validity and reliability, with a Cronbach’s Alpha coefficient of 0.887. The key findings indicate a significant positive relationship between absenteeism and productivity, with a regression coefficient of 0.575 and a significance level of p < 0.05. The coefficient of determination (R²) was 45.4%, suggesting that nearly half of the variation in productivity can be explained by absenteeism levels. The primary causes of absenteeism were identified as health-related issues, family responsibilities, and dissatisfaction with the working environment. These findings provide valuable insights for company management in implementing preventive health programs, adopting flexible work policies, and enhancing both the physical and psychological aspects of the workplace to reduce absenteeism and boost productivity. Moreover, this study contributes to the advancement of human resource management literature, particularly in the area of managing attendance and productivity within the manufacturing industry context.